2021
DOI: 10.1038/s41467-021-23408-1
|View full text |Cite
|
Sign up to set email alerts
|

The P-type ATPase transporter ATP7A promotes angiogenesis by limiting autophagic degradation of VEGFR2

Abstract: VEGFR2 (KDR/Flk1) signaling in endothelial cells (ECs) plays a central role in angiogenesis. The P-type ATPase transporter ATP7A regulates copper homeostasis, and its role in VEGFR2 signaling and angiogenesis is entirely unknown. Here, we describe the unexpected crosstalk between the Copper transporter ATP7A, autophagy, and VEGFR2 degradation. The functional significance of this Copper transporter was demonstrated by the finding that inducible EC-specific ATP7A deficient mice or ATP7A-dysfunctional ATP7Amut mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 79 publications
2
39
0
Order By: Relevance
“…However, our data ruled out defects in VEGFR2 transcription. As for VEGFR2 degradation, this process depends on autophagy, the inhibition of which can increase VEGFR2 levels and angiogenesis [ 22 ]. While we confirmed that Dox increased autophagic flux [ 23 ], inhibition of autophagy or of the proteasome did not restore VEGFR2 levels in Dox-treated HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…However, our data ruled out defects in VEGFR2 transcription. As for VEGFR2 degradation, this process depends on autophagy, the inhibition of which can increase VEGFR2 levels and angiogenesis [ 22 ]. While we confirmed that Dox increased autophagic flux [ 23 ], inhibition of autophagy or of the proteasome did not restore VEGFR2 levels in Dox-treated HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…PLVAP+ ECs were also identified in different peripheral clusters, suggesting that they originally formed an intermediate subpopulation that migrated into the tumor core. Moreover, the tumoral ECs’ cluster expresses VEGFR2, a molecule that facilitates the communication of blood vessels with tumor hepatocytes, promoting angiogenesis [ 141 ]. A comparative study of TAEs with LSECs demonstrated phenotypic differences related to angiogenesis modulation.…”
Section: Tumor Microenvironment In Hcc: the Importance Of The Nichementioning
confidence: 99%
“…Increasing evidence has unraveled that angiogenesis is crucial for tumour progression and is highly dependent on VEGF expressed by most malignant tumours [25][26][27] . Additionally, FRS2-mediated signals were validated to promote tumour angiogenesis and predict poor prognosis in prostate carcinoma, high-grade serous ovarian cancer and liposarcoma [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%